Knowledge of Ghana’s liberal abortion law and use of modern contraceptives among women of reproductive age - Kumbeni, Maxwell Tii; Luck, Jeff; Harvey, S. Marie (Reproductive health, 2025)
Background Modern contraceptives have been widely promoted as an effective tool for birth control. They are highly effective for preventing unintended pregnancies thereby reducing the risk of abortions, maternal morbidities, and mortalities. Abortion or planned abstinence from sexual intercourse may be perceived as alternatives to the use of modern contraceptives. The aim of this study was to assess whether knowledge of the legal status of abortion, and knowledge of the monthly fertile period, were associated with the use of modern contraceptives among women of reproductive age in Ghana. Methods We used nationally representative secondary data from the 2017 Ghana Maternal Health Survey. A weighted sample of 23,466 non-pregnant women aged 15–49 years were included in the study. Pearson chi-square and multivariable logistic regression analysis were conducted to assess the association between the independent and the outcomes variables. Sampling weight, cluster, and strata were applied at all levels of the analysis. Results More than half (55.4%) lived in urban area, 80.1% were 20 years or older, 52.2% were multiparous women, 61.9% had secondary or higher education, and 34.5% were in the lower two wealth quintiles. We found no statistically significant association between knowledge of the legal status of abortion and use of modern contraceptives, or between knowledge of the monthly fertile period and use of modern contraceptives. Women with history of an induced abortion were 1.57 times as likely to use modern contraceptives compared to those with no history [adjusted odds ratio (aOR) 1.57, 95% CI 1.41–1.75]. Each additional increase in knowledge of a different modern contraceptive method was associated with 1.25 times increase in modern contraceptive use (aOR 1.25, 95% CI 1.22–1.29). Conclusions Intensifying education on modern contraceptive methods and use, especially at abortion facilities, may help improve the uptake of modern contraceptives among women in Ghana. Plain Language Summary Modern contraceptive use is known to have positive health benefits for women, their children and the entire family. When used correctly and consistently, it is effective in preventing unplanned pregnancies and abortion related complications among women. However, the prevalence of modern contraceptive use has been consistently low in Ghana. Previous studies have identified socio-demographic and health services related factors as affecting the use of modern contraceptives among women in Ghana. Our study used a nationally representative survey data to assess how knowledge of the abortion law in Ghana and knowledge of monthly menstrual period might affect the use of modern contraceptives among women in Ghana. We found that women’s knowledge of the abortion law in Ghana and knowledge of their monthly menstrual period were not associated with the use of modern contraceptives. However, knowledge of more than one different modern contraceptive methods and history of an induced abortion were associated with higher utilization of modern contraceptives among women in Ghana. Intensifying education on modern contraceptive methods and use, especially at abortion clinics, may help improve the of modern contraceptives among women in Ghana.